Length-Based Assessment of Fish Stocks in a Data-Poor, Jointly Exploited (China and Vietnam) Fishing Ground, Northern South China Sea - Zhang, Kui; Li, Jiajun; Hou, Gang; Huang, Zirong; Shi, Dengfu; Chen, Zuozhi; Qiu, Yongsong (Frontiers in Marine Science, 2021)
The Beibu Gulf is one of the most important fishing grounds in the South China Sea (SCS), and the fisheries resources in this area are exploited by both China and Vietnam. In recent decades, some indications of overfishing have appeared, including declining catch rates, frequently changing catch composition, and shrinking body sizes in main commercial fish species. Due to limited data availability, only a small subset of exploited fish stocks in this area has been assessed. Here, we applied two length-based methods, electronic length frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB), to stock assessment of nine exploited fish species in the Beibu Gulf. There were total 53, 652 length records of 30 target stocks used in this study during the survey period from 1960 to 2015. The results showed that the two length-based methods presented different ability in estimating exploitation rate (E), and the estimated E ranged from 0.34 to 0.87 using ELEFAN method while ranged from 0.26 to 0.86 using LBB method. The prior information from ELEFAN method was effective for LBB method, as there were significant differences in 66.7% of the 30 target stocks in estimated Linf, and 93.3% in estimated B/BMSY, using LBB method with and without prior information. The estimated Lc/Lc_opt and B/BMSY of LBB method suggest a pressing situation for the fisheries in the Beibu Gulf, as 86.7% of the 30 target stocks had been suffering from growth overfishing (Lc/Lc_opt < 1), and 83.3% had been overexploited or fully exploited (B/BMSY ≤ 1.2). In addition, we suggest using both ELEFAN and LBB methods to fit length-frequency data of data-poor fish stocks because they are complementary in estimating management reference points. We also emphasize collaboration mechanism should be established by China and Vietnam for the sustainability and recovery of fishery resources in the Beibu Gulf.